LEADER MEMBER EXCHANGE DAN KEPRIBADIAN UNTUK MENINGKATKAN EMPLOYEE VOICE KOPONTREN DT - Rahmawati, Putri; Sumiyati, Sumiyati; Masharyono, Masharyono (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2016)
ABSTRACTPurpose – this study was conducted to see how much influence leader member exchange and personality to employee voiceDesign/methodology/approach – this type of research This research uses descriptive and  verification method, with explanatory survey. Saturated sample of nonprobability sampling was used in sampling technique which amounted to 47 people. Multiple correlation was used in data anlysis technique.Findings – based on the result of research that the employee voice is affected by leader member exchange and personality.Orisinality – the difference in this study with other study located from independent variable, the object of research, population and sample, measurment, and as well as research result, the resource of theory from journals and books, so the theory used is different. Keywords              : Leader Member Exchange, personality,, Employee Voice, communication, employee relation, organization effectiveness.